Antioxidant potential of 10 yacon Smallanthus sonchifolius (Poepp. & Endl.) H. Robinson accessions native from Cajamarca – Peru - Arnao, Inés (2011)
Yacon (Smallanthus sonchifolius) is part of our food and medicinal biodiversity and both roots and leaves are used due to their antioxidant, hypoglycemic and antibacterial properties. Consequently its use as functional food and/or nutraceutical is promising. Objectives: To determine the antioxidant capacity of 10 yacon accessions native from Cajamarca. Design: Descriptive, cross sectional and prospective study. Setting: Biochemistry and Nutrition Research Center, Faculty of Medicine, Universidad Nacional Mayor de San Marcos (UNMSM), and Universidad Nacional de Cajamarca (UNC), Peru. Biological material: Yacon leaves and roots. Interventions: Yacon leaves and roots of plants cultivated in the Experimental Field of the Roots and Andean Tubers Program, Cajamarca's city (2 536 meters above sea level), were used, from the collection that supports the UNC Faculty of Agrarian Sciences. Origin of these accessions were Yanamango, Chuquibamba, Yanac, Cumbico, Bambamarca, Sapuc, Can Can, Jose Galvez, Contumaza, and San Ignacio. DPPH's (1,1-difenil-2-picrilhidrazil) test was used and phenol and flavonoid total content was measured. Ascorbic acid, gallic acid (AG) and quercetin (Q) were used as reference. Main outcome measures: Total phenol and flavonoid content. Results: Root extracts radical DPPH capture presented an IC50, range 1,92-6,32 uL of root/mL, and its total phenols varied from 217,5-352,4 ug EAG/mL of root. Leaves hydroalcoholic extracts showed an IC50 for radical DPPH capture between 44,2-110,3 ug of dry leaf/mL. Its total phenols ranged between 7,7-22,7 mg EAG/g of leaf and flavonoids between 2,2-4,4 mg EQ/g of leaf. Conclusions: In the present study, accessions with major antioxidant potential for leaves and roots came from Yanamango and Chuquibamba. These results might relate to different geographical distribution